Study of the magnetic and electrical properties of pinal ferrite type using network analyzer - علي يسر, هاشم; يوسف ثامر, رسل; عبد ياسر, حسن (University of Thi-Qar Journal of Science, 2016)
In this work, the spinal ferrite  has been prepared where  ,  used. as radar absorbing materials (RAM). Conventional ceramic techniques method was used to prepare these materials at  microwaves with the range of frequencies (8-12) GHz. The absorption for microwaves was examined by the utilized the network analyzer. The relationship between reflectivity, absorption and attenuation coefficient were plotted as a function of frequency, and sintered at a temperature . The results showed the emergence of several resonance peaks at , samples showed high Absorbency in contrast low reflectivity and high values of attenuation coefficient at the same frequencies, this is due to domain rotation as well domain wall motion of the ferrite. The values of the real and imaginary parts of relative magnetic Permeability and relative electric permittivity were measure for all samples. The results revealed the apparent resonance peaks at same frequencies that apparent at absorption and reflectivity curves of the same samples. X-ray diffraction tests were made for one sample and result showed the structure of the sample is polycrystalline.